Reminder dengan Short Message Service (SMS) Untuk Meningkatkan Kepatuhan Kunjungan K4 dan Kemampuan Deteksi Dini Tanda Bahaya Ibu Hamil Trimester III - Dewi Afidatul Ummah; Gita Kostania; Rosalina Rosalina (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Low K4 rate coverage and management of complications in pregnancy is a problem in Klaten, caused by lack of information and motivation in antenatal care. Short Message Service (SMS) can be used as a support intervention to increase information. This research aims to determine effects of SMS toward K4 compliance and screening danger sign ability among third trimester pregnancy in Wedi Public Health Center. Methods: type of research is a quasy experimental with post-test only non-equivalent control group. The sampling technique used Quota sampling, obtain 52 respondents in the third trimester of pregnancy. Data analysis techniques used Mann Whitney and Chi Square with a significance level of 0.05. Result: K4 compliance of pregnancy could be classified as disobedient of 59,6% and screening danger sign ability among third trimester pregnancy is considered relatively of 53.8%. SMS had a strong impact toward K4 compliance with a p value= 0,002 (p<0,05). SMS also affected screening danger sign ability among third trimester pregnancy with a p value = 0.001 (p<0.05). Conclusion: There is significant effects between SMS toward K4 compliance and screening danger sign ability among third trimester pregnancy in Wedi Pubic Health Center, Klaten Regency.